The genus Cultroribula (Acari: Oribatida: Astegistidae) in Mongolia, with new findings from Altai Mountains and remarks on known species of the world - Bayartogtokh, Badamdorj (Zootaxa, 2012)
The oribatid mite genus Cultroribula Berlese, 1908 is represented in Mongolia with six species. Most species of Cultroribulafound in Mongolia are inhabitants of litter of various types of forests, soils of steppes and the high mountain alpine zone, butare also commonly found in lichens growing on trees or bare rock and terricolous bryophytes. In this work, two species, Cul-troribula altaica sp. nov. and Cultroribula rarisetosa sp. nov., are described as new to science based on adults collected fromlitter of cool temperate forests and lichens growing on bare rock, respectively, in western Mongolia. In addition, two knownspecies, Cultroribula berolina Weigmann, 2006 and Cultroribula vtorovi Krivolutsky, 1971 are redescribed. Cultroribula bero-lina is recorded for the first time for the fauna of Asia. Species descriptions are accompanied with detailed illustrations. Data ongeographical distribution and habitat ecology are given for all known species in the world. Issues concerning the taxonomic sta-tus of some genera of Astegistidae and species of Cultroribula are discussed. The subgenus Furcoppia (Mexicoppia) is consid-ered as a junior synonym of Cultroribula. The new combination, Cultroribula hauseri (Mahunka, 1983) for Furcoppia(Mexicoppia) hauseri Mahunka, 1983 is proposed. Furthermore, a key is provided for the identification of adults of the known species of Cultroribula in Mongolia.